Language Game in Advertising and Its Impact on Consumers - Anna E. Bazanova; Mohamed Alsadig Hamid Musa (RUDN Journal of Language Studies, Semiotics and Semantics)
The concept and phenomenon of a language game, its main functions, types and application in commercial advertising is a way to attract the attention of consumers and promote a product. Examples of phonetic, morphological and syntactic wordplay in the texts of English-language commercial advertising are analyzed. The purpose of the article is to analyze the techniques of a language game and identify their functional features at various levels in an English-language advertising text. In this article, the following methods were used: descriptive-analytical method, interpretation method, search method. When choosing a material for analysis, the method of continuous sampling was used. As the material of the research, we used English-language advertisements in various resources, such as from magazines and newspapers and videos, in which a language game was revealed. Thus, the language game implemented in advertising texts is an important phenomenon, since it contributes to the maximum impact on the consumer, since the recipient, thanks to his techniques and functions, draws attention to this advertisement. In addition, an advertisement in which a language game as present is an indicator of a high level of the consumer’s language competence.